Insulin resistance and its association to carotid subclinical atherosclerosis. - Abdel del Busto Mesa; Julio Oscar Cabrera-Rego; Julio C. Gandarilla Sarmientos; Juan Valiente Mustelier (ECIMED, 2011)
Objective To determine the association between insulin resistance and the presence ofcarotid subclinical atherosclerosis.Method We conducted a cross-sectional study that included 239 patients with suspicionof carbohydrates metabolism disorders, in collaboration between theEndocrinology National Institute and the Cardiology and Cardiovascular SurgeryInstitute. We included clinical (age, sex, personal antecedents of smokinghabit, high blood pressure and dislipidemia, systolic and diastolic bloodpressure), anthropometric (waist circumference and body mass index), biochemical(total cholesterol, C-HDL, C-LDL, triglycerides) and ultrasonographic(carotid intima-media thickness and carotid plaque presence) variables.Results Systolic (r=0,159, p=0,015) and diastolic blood pressure ( r=0,197,p=0,002), body mass index (r=0,314, p=0,000), waist circumference(r=0,380, p=0,000), triglycerides (r=0,143, p=0,028) and carotid intimamediathickness (r=0,145, p=0,027) showed a positive and significant correlationwith HOMA-IR. A significant increase in the presence of carotid intima-media thickness ≥75 percentile according to age, sex and race wasshown for the insulin resistance group (58,1 % vs 34,2 %, p=0,000 OR 2,92[2,00-4,25]).Conclusions Insulin resistance showed a positive and significant correlation with carotidintimae-media thickness.